Metadiscourse in Academic Written and Spoken English: A Comparative Corpus-Based Inquiry - Vasheghani Farahani, Mehrdad (Research in Language, 2020)
This paper reports on a comparative study performed in the field of Corpus Linguistics. The objective of the research was to analyze the distributional pattern of interactive and interactional metadiscourse features in two modes of academic spoken and written English. For this reason, a list of metadiscourse characteristics was gathered. By using the Sketch engine software, all the words were scrutinized in the corpus and their concordance lines were analyzed one by one in both corpora (British Academic Written English Corpus and British Academic Spoken English Corpus). As the data can show, in both corpora, the general propensity of the authors was towards the interactive metadiscourse features. In addition, in the written corpus, the transitions and endophoric markers were used more often; while in the spoken, endophoric markers and transitions were the most frequently applied metadiscourse features. In the interactional metadiscourse features, hedges and self-mentions were the most frequent in the written form; whereas in the spoken, self-mentions and boosters were used moe often.